PENGARUH UKURAN PERUSAHAAN DAN UKURAN KAP TERHADAP AUDIT DELAY DENGAN SPESIALISASI INDUSTRI AUDITOR SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Infrastruktur, Utilitas, danTransportasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2016) - Mutiara adhilla Damanik; Hardi Hardi; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of This research is to examine the effect of Firm Size, Kap Size to Audit Delay with Auditor Industry Specialization as moderating variable. The population is all infrastructure, utility and transportation companies listed in Bursa Efek Indonesia in years 2015-2016. This research is included in quantitative research. The type of data used in this research is secondary data from financial statement of the aforementioned infrastructure, utility and transportation companies and data derived from the IDX fact book and Indonesian Capital Market Directory, sampling is done by the method of purposive sampling is the technique of sampling with certain considerations. The total of samples is 28 firms. These data were analyzed using multiple regression analysis with SPSS Version 17. The results of this research showed that Firm Size affects Audit Delay with significant value 0,040, KAP Size affects Audit Delay with significant value 0,000, Firm Size affects Audit Delay after moderated Auditor Industry Specialization with significant value 0,000 and KAP Size affects Audit Delay after moderated Auditor Industry Specialization with significant value 0,010. So the conclusion of this research is all hypothesis presented acceptable.Keywords : Audit Delay, Firm Size, KAP Size, Auditor Industry Specialization